2021
DOI: 10.1200/jco.2021.39.15_suppl.8535
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and immunologic characterization of large-cell neuroendocrine carcinoma of the lung.

Abstract: 8535 Background: Large-cell neuroendocrine carcinoma (LCNEC) is a rare type of lung cancer with a poor prognosis. Due to its rarity, molecular characterization of LCNEC is not well elucidated. We aim to understand the genomic and immunologic landscape of LCNEC to identify molecular alterations and relevant biological pathways with potential therapeutic value. Methods: Comprehensive profiling including whole exome sequencing (WES), next-generation sequencing (NGS), whole transcriptome sequencing (WTS), and imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The situation is similar in other hgNECs, aside from rare actionable oncogenic mutations (e.g. KRAS G12C) occasionally observed in pulmonary LCNEC 14 .…”
Section: Introductionsupporting
confidence: 58%
“…The situation is similar in other hgNECs, aside from rare actionable oncogenic mutations (e.g. KRAS G12C) occasionally observed in pulmonary LCNEC 14 .…”
Section: Introductionsupporting
confidence: 58%
“…Studies investigating the molecular characteristics of pulmonary LCNEC have revealed two major subtypes (10,11): small-cell lung cancer (SCLC)-like LCNEC characterized by co-alterations in TP53 and RB1, and NSCLC-like LCNEC characterized by harboring NSCLC-type mutations. Targetable genomic alterations such as EGFR mutations, KRAS G12C mutations, BRAF V600E mutations, and ALK fusions have been identified in LCNEC (8)(9)(10)(11)(12), though at lower rates compared with lung adenocarcinoma. Response to matching targeted therapy has been reported for EGFR mutations (13,14), BRAF V600E mutation (15), and ALK fusions (16,17), suggesting the role of targeted therapy in driver mutationpositive LCNEC.…”
Section: Discussionmentioning
confidence: 99%
“…LCNEC is associated with poor prognosis, with median overall survival less than a year in patients with stage IV disease ( 5 , 6 ). Although not common, targetable genomic alterations such as alterations to EGFR , BRAF , and ALK are also seen ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al. ( 41 ) performed comprehensive molecular characterization (NGS, whole-transcriptome sequencing, and IHC) of a cohort of 467 LCNECs, and ALK fusions were identified in 1.7% of the cases. In a case series, published by Zheng et al.…”
Section: Discussionmentioning
confidence: 99%